Gender-transformative food and nutrition training workshop report - Embu County - Lutomia, Cosmas Kweyu; Nyamolo, Victor; Muriithi, Catherine; Ketema, Dessalegn; Nyaga, John Ndwiga; Njeru, Patrick Ndwiga; Nchanji, Eileen (2025)
On 7 August 2025 in Embu, county officers, extension teams, KALRO and farmers met for a gender-transformative nutrition training. Using local examples, role-plays and small group discussions, participants mapped who buys, cooks and eats, identified seasonal gaps and taboos, and discussed fairer sharing. They worked with the ten food groups and linked them to kitchen gardens, intercropping, and biofortified crops. Agreed follow-ups include peer learning, preservation demos, and integrating nutrition messages into routine extension activities.